2021
DOI: 10.1007/s00167-020-06375-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation, MRI and clinical outcome scores do not accurately predict an important meniscal tear in a symptomatic discoid meniscus

Abstract: PurposeDiscoid menisci can be symptomatic from instability or a tear. A torn discoid meniscus is likely to require repair to preserve meniscal function and should not be missed. This is the first study to evaluate a range of pre‐operative methods to predict the likelihood of a torn discoid meniscus. MethodsA retrospective analysis of prospectively collected data was performed. Clinical, radiographic and operative data were reviewed. Patients were grouped based on the presence of a tear or not during surgery. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…17 Our rate of bilateral discoid medial menisci was substantially lower at 1 of 21 patients. We did have 1 patient with discoid medial and lateral menisci, as did Jeannopoulos, 24 and 1 of 13 patients also had a discoid lateral meniscus as well as a discoid 20 34/39 3/39 6/39 Sabbag (2018) 35 60 12/60 Kang (2019) 25 47/60 23/60 15/60 36/60 Hampton (2021) 21 27/32 2/32 19/32 Hesse (2021) 23 71/78 30/71 Lins (2021) 27 25/30 {{ medial meniscus in the same knee in the study by Chen et al 10 Specifically, Chen et al 10 reported on 13 operatively treated patients with discoid medial menisci over a 43-year period at 1 hospital. Most of the 13 patients had knee pain and mechanical symptoms and signs.…”
Section: Discussionmentioning
confidence: 84%
“…17 Our rate of bilateral discoid medial menisci was substantially lower at 1 of 21 patients. We did have 1 patient with discoid medial and lateral menisci, as did Jeannopoulos, 24 and 1 of 13 patients also had a discoid lateral meniscus as well as a discoid 20 34/39 3/39 6/39 Sabbag (2018) 35 60 12/60 Kang (2019) 25 47/60 23/60 15/60 36/60 Hampton (2021) 21 27/32 2/32 19/32 Hesse (2021) 23 71/78 30/71 Lins (2021) 27 25/30 {{ medial meniscus in the same knee in the study by Chen et al 10 Specifically, Chen et al 10 reported on 13 operatively treated patients with discoid medial menisci over a 43-year period at 1 hospital. Most of the 13 patients had knee pain and mechanical symptoms and signs.…”
Section: Discussionmentioning
confidence: 84%
“…The sensitivity and specificity of this criterion are 95% and 97%, respectively 100,101 . In addition, MRI has a certain diagnostic value in classification, tear type and location, and peripheral rim stability of DLM 48,95,102–107 . The diagnostic specificity and sensitivity of MRI in adult DLM tears are 100% and 97.8%, 108 but in children's DLM and its lesions are still controversial 47,109,110 …”
Section: Resultsmentioning
confidence: 99%
“…100,101 In addition, MRI has a certain diagnostic value in classification, tear type and location, and peripheral rim stability of DLM. 48,95,[102][103][104][105][106][107] The diagnostic specificity and sensitivity of MRI in adult DLM tears are 100% and 97.8%, 108 but in children's DLM and its lesions are still controversial. 47,109,110 In patients with unilateral symptomatic DLM, the probability of DLM in the contralateral knee is about 73%-97%, 6 and of the same type in both is 88%.…”
Section: Diagnostic Value Of Mri On Dlm and Its Classification Andmentioning
confidence: 99%
“…Furthermore, more than 12% of children still experience motion artefacts after sedation, which may cause severe complications such as cardiopulmonary depression and brain development 19. Moreover, significant differences exist in the morphology and vascular distribution of DLM between children and adults, which may influence the diagnostic value of MRI for DLM in children 20 21. Therefore, the feasibility and efficacy of MRI for DLM diagnosis in children remain controversial, and exploring a new technique to solve this dilemma is necessary.…”
Section: Introductionmentioning
confidence: 99%